Hypertension Causes, Impacts, and Control Strategies In The Modern Era - Abdul Thalib (Ammar Dharma Foundation, 2025)
Background: Hypertension, or high blood pressure, is a global health problem that affects about 1.13 billion people worldwide. According to the World Health Organization (WHO), hypertension is a major risk factor for cardiovascular disease, stroke, and premature death. The disease is often asymptomatic, so many individuals are unaware of their condition until serious complications occur. Therefore, a better understanding of the causes, impacts, and control strategies of hypertension is essential.Objective: The aim of this study is to understand the causes, impacts, and control strategies of hypertension in order to reduce its prevalence and improve individuals' quality of life.Methods: This literature review is conducted by collecting and analyzing relevant scientific studies and articles on hypertension. The sources used include medical journals, reports of health organizations, and clinical guidelines published between 2003 and 2024. The literature selection process was carried out using keywords such as